Self-Directed on English Language Learning During Covid-19 Pandemic: Analysis of Teacher Perceptions and Student Learning Autonomy - I Made Hardi Setiawan; Luh Putu Artini (Universitas Pendidikan Ganesha, 2021)
Online learning causes students to learn more independently. This study aims to analyze the perception of English teachers about independent learning, describe the activities provided by the teacher in online learning, and identify the components of independent learning that can be identified in online learning activities. This research is qualitative. The research subjects in this study were English teachers who applied online learning. Data collection was carried out using questionnaires, observations, and identification tables. Questionnaires were used to collect data on English teachers' perceptions of self-learning. There are three questionnaires to collect teacher perception data; 1) Teachers' perceptions of SDL content knowledge, 2) teachers' perceptions of SDL implementation, and 3) teachers' perceptions of the impact of SDL. Observation is used to collect data on activities assigned by the teacher in online learning. The data is described into three segments, pre-activity, while-activity, and post-activity. The results showed that teachers claimed to know about self-directed learning, often applied SDL, and claimed SDL had a very influential impact on students. Teachers still have difficulty handling online learning, especially in pre-activities and post-activities. In this study, there is a discrepancy between the teacher's perception and real action. Of the seven indicators, teachers can only apply two indicators. There are indications that the application of self-directed learning in online learning has not been effective. Based on the study results, it can be concluded that English teachers still have difficulty implementing independent learning to increase student learning independence, especially in online learning.